Determinan Utang Luar Negeri Indonesia Tahun 1981-2020 - Rina Dwi Octavianti; Budyanra Budyanra (Department of Statistics ITS, 2023)
Indonesia is one of the developing countries that is actively advancing development. However, limited funding for development is the main obstacle for developing countries, including Indonesia, in increasing development. To overcome these cost problems, a large injection of funds is needed, one of which comes from foreign debt. Although foreign debt helps to advance development, its uncontrolled increase will result in default on debt payments until a crisis occurs. Theoretically, foreign debt is influenced by various faktors including foreign investment (FDI), gross domestic product (GDP), exchange rates, imports, exports, and foreign exchange reserves. This study aims to analyze the effect of FDI, GDP, exchange rate, imports, exports, and foreign exchange reserves on Indonesia's foreign debt in the long term and short term. The analytical method used in this study is the Error Correction Mechanism (ECM) for the period 1981-2020. The results of the study indicate that in the long term and short term the variabels of FDI, foreign exchange reserves, and the exchange rate have a significant and positive effect on Indonesia's foreign debt. Meanwhile, the variabels of GDP, imports, and exports have no significant effect on Indonesia's foreign debt in the long and short term.